PENGARUH MODEL PEMBELAJARAN PROJECT BASED LEARNING TERHADAP KREATIVITAS MENULIS PUISI PELAJARAN BAHASA INDONESIA SISWA KELAS IV SD NEGERI 5 LAPPA KABUPATEN SINJAI - Aulia Nurul Azizah Abbas; Nur Abidah Idrus; Nurfaizah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims (1) to describe the implementation of the Project Based Learning (PjBL) model in the Indonesian Language subject for fourth-grade students at SD Negeri 5 Lappa, Sinjai Regency, (2) to describe students’ poetry writing creativity, and (3) to determine the effect of the Project Based Learning (PjBL) model on students’ poetry writing creativity. This study used an experimental method with a quantitative approach. The research design was a Quasi-Experimental design with a nonequivalent control group design. The population consisted of all fourth-grade students of SD Negeri 5 Lappa, Sinjai Regency. The sample included 22 students from class IVA and 22 students from class IVB selected through total sampling. Data were collected using poetry writing creativity tests, observation sheets, and documentation. Data were analyzed using descriptive and inferential analysis. The results showed that: (1) the implementation of the Project Based Learning (PjBL) model in the experimental class was categorized as very good, as indicated by the improvement in teacher and student observation results from fairly good in the first meeting to very good in the second meeting; (2) students’ poetry writing creativity in the experimental group was higher than in the control group, as shown by higher posttest scores; and (3) there was a significant effect of the Project Based Learning (PjBL) model on students’ poetry writing creativity because the probability value was smaller than 0.05.